THE INTEGRATING INTERCULTURAL COMPETENCE INFUSED ENGLISH READING MATERIALS FOR 10TH-GRADE STUDENTS: A NEED ANALYSIS - Anjani, Suci Dhea; Sulistyaningrum, Siti Drivoka (STKIP Persada Khatulistiwa Sintang, 2024)
The educational sector is gaining significant interest in intercultural competency due to its potential to enhance students' global learning experiences and academic performance. In this study, a needs analysis was used to investigate the existing learning materials of the needs of 10th-grade students in intercultural competence for English reading materials. The primary goal of this research is to analyze the English reading materials currently used by 10th-grade students and evaluate the extent to which they incorporate intercultural competence. In addition, the results of the need analysis show the gap between the current materials and intercultural competence. However, the result also found that students need teaching materials that contain intercultural values. These values are taken from international, national, and local cultures.Â Therefore, it indicates an urgency to integrate new English reading materials that promote intercultural materials to facilitate the needs of students.